2009
DOI: 10.1111/j.1553-2712.2009.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Visual Analog Scale to Rate and Monitor Severity of Nausea in the Emergency Department

Abstract: Objectives: The objective was to describe the association between verbal descriptors of nausea severity and visual analog scale (VAS) ratings in an undifferentiated emergency department (ED) population and to calculate the minimum clinically significant difference (MCSD) in VAS rating of nausea severity in this population.Methods: A prospective observational study was conducted at three EDs on a convenience sample of stable, consenting adult patients presenting with nausea as part of their symptom complex. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 26 publications
7
67
0
Order By: Relevance
“…Many pharmacologic therapies that are prescribed in the context of pregnancy are not specifically approved for use in a gravid population. 11,20 Although another study using the same database reported an association between filling a prescription for ondansetron and heart defects in the offspring, these data have only been presented in abstract form and cannot be used to establish causation. Nonpregnant patients have shown dramatic responses to this antiemetic, with up to 50% reduction in vomiting when compared with conventional treatments, which has led to prescribing ondansetron during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many pharmacologic therapies that are prescribed in the context of pregnancy are not specifically approved for use in a gravid population. 11,20 Although another study using the same database reported an association between filling a prescription for ondansetron and heart defects in the offspring, these data have only been presented in abstract form and cannot be used to establish causation. Nonpregnant patients have shown dramatic responses to this antiemetic, with up to 50% reduction in vomiting when compared with conventional treatments, which has led to prescribing ondansetron during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] There are no well-validated tools to measure nausea or vomiting associated with pregnancy. A VAS was used because it correlates well with numerical and verbal descriptors of nausea and has been used in the oncology, emergency medicine, and anesthesia literature to investigate the efficacy of anti-emetic medications.…”
Section: Methodsmentioning
confidence: 99%
“…35 This sample size would have Ͼ90% power at the 0.01 level of significance to detect a clinically important difference of 2.2 cm in VAS-N for the other 2 hypotheses. 36 We assumed the SD of treated nausea on the VAS-N scale in children is similar to that in adults (2.35 cm) 15,17,36 and that a 1-face difference in the pictorial scale would be considered clinically significant. 37 Spearman's correlation coefficients were calculated between the first paired scores on the VAS and pictorial scales to avoid using scores from the same patient twice.…”
Section: Sample Sizementioning
confidence: 99%
“…This scale has been validated as a reliable tool for a semi-quantitative assessment of acute pain and nausea in a wide variety of ED patients. 18-24 …”
Section: Methodsmentioning
confidence: 99%